SP0179 Transition Care Programmes: A North American Perspective. (15th July 2016) - Tucker, L.
Abstract : Adolescents with rheumatic diseases frequently continue to require rheumatologic care into adulthood, either due to continued active disease and requirement for treatment, or management of sequelae of disease. In addition, these vulnerable adolescents need to manage transition in schooling, work, living situation, health insurance coverage, and peer relationships. In the recent years, there has been increased focus on improving transition support to adolescents with chronic diseases, resulting in a variety of specialized programs and resources. Objectives for this talk are: a) To describe North American transition guidelines and models for youth with rheumatic diseases, and how these are applied across different centres and regions. b) To compare transition practices in pediatric rheumatic programs in North America. c) To review new transition planning resources for use in the pediatric rheumatology setting. Disclosure of Interest: None declared